(untitled) (Transport systems and technologies, 2023)
The paper deals with the topical scientific task concerning substantiation of rational parameters of express mode of transportation in terms of city bus routes. That helps reduce passengers’ time spent for travelling, increase a degree of use of transportation modes as well as favour significant cost reduction for fuel and decrease the amount of harmful emissions in the urban atmosphere. Analysis of the available methods and approaches to the organization of express mode of bus traffic in terms of local routes has helped identified that they do not consider to the full extent the interests of all the traffic participants or have narrow range of application. Those are the facts that limit considerably wide implementation of express mode irrespective of its great potential as for increasing the efficiency of local passenger transportation. Conditions of expedient implementation of express mode of transportation for buses on local routes have been identified basing on the parameters of passenger flow. The developed method of the formation of a list of stops to be serviced by buses operating in the express mode, takes into consideration the irregular nature of passenger flow and intervals of daily bus traffic respectively. Basing on the economic, social, and environmental indices of efficiency of a transportation process, the developed method of identifying rational parameters of express mode of traffic on local bus routes considers dynamic distribution of passenger correspondences between the standard and express route depending on the number of buses and a list of express route stops. А technical and operational assessment of the implementation of the express mode of bus traffic on city route #70 in Dnipro was performed.